GRAPHIC DESIGN IN THE CREATIVITY DEVELOPMENT OF STUDENTS AT THE TAHFIDZ AL-QURAN ISLAMIC BOARDING SCHOOL "OEMAH AL-QURAN" MERJOSARI LOWOKWARU MALANG - Hasibuan, Albar; Chanifah, Nur; Fitrahayunitisna; Hambali, Muhammad; Muhammad Noor, Aditia (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
As an educational institution, Islamic boarding schools are required to carry out significant acceleration and transformation. If in the past the scope of output was limited to the religious dimension, now pesantren graduates are expected to be able to contribute a lot in various aspects of people's lives. The development of applications in the field of information technology has a major impact in various fields of life, including in the creative industries such as printing, digital image processing and graphic design. This requires us to provide training to students so that they can follow developments and be able to use it for preparation after they graduate. Training on the use of these applications is important to equip students' creativity so that later when they leave the boarding school, they can develop these skills to be more independent. Even these skills can also equip students for entrepreneurship, so they can support their economy. Based on this reality, the MPK Center Community Service Team initiated to assist Islamic boarding schools in developing students' creativity through graphic design training. This is because the human resources owned by Islamic boarding schools in the field of graphic design are minimal or even non-existent. With the graphic design training, it is hoped that it can help pesantren in equipping students with skills so that their creativity is formed.